Intermittent pneumatic compression is a cost-effective method of orthopedic postsurgical venous thromboembolism prophylaxis - Saunders R; Comerota AJ; Ozols A; Torrejon Torres R; Ho KM (Dove Medical Press, 2018)
Rhodri Saunders,1 Anthony J Comerota,2 Audrey Ozols,3 Rafael Torrejon Torres,1 Kwok Ming Ho4 1Coreva Scientific, Freiburg, Germany; 2Jobst Vascular Institute, Toledo, OH, USA; 3Medtronic, Boulder, CO, USA; 4Royal Perth Hospital and School of Population Health, University of Western Australia, Perth, WA, Australia Background: Venous thromboembolism (VTE) is a major complication after lower-limb arthroplasty that increases costs and reduces patient’s quality of life. Using anticoagulants for 10–35 days following arthroplasty is the standard prophylaxis, but its cost-effectiveness after accounting for bleeding complications remains unproven. Methods: A comprehensive, clinical model of VTE was created using the incidences, clinical effects (including bleeding), and costs of VTE and prophylaxis from randomized controlled trials, meta-analyses, and large observational studies. Over 50 years, the total health care costs and clinical impact of three prophylaxis strategies, that are as follows, were compared: low-molecular-weight heparin (LMWH) alone, intermittent pneumatic compression (IPC), and IPC with LMWH (IPC+LMWH). The cost per VTE event that was avoided and cost per quality-adjusted life year (QALY) gained in both the US and Australian health care settings were calculated. Results: For every 2,000 patients, the expected number of VTE and major bleeding events with LMWH were 151 and 6 in the USA and 160 and 46 in Australia, resulting in a mean of 11.3 and 9.1 QALYs per patient, respectively. IPC reduced the expected VTE events by 11 and 8 in the USA and Australia, respectively, compared to using LMWH alone. IPC reduced major bleeding events compared to LMWH, preventing 1 event in the US and 7 in Australia. IPC+LMWH only reduced VTE events. Neither intervention substantially impacted QALYs but both increased QALYs versus LMWH. IPC was cost-effective followed by IPC+LMWH. Conclusion: IPC and IPC+LMWH are cost-effective versus LMWH after lower-limb arthroplasty in the USA and Australia. The choice between IPC and IPC+LMWH depends on expected bleeding risks. Keywords: VTE, IPC, thromboprophylaxis, arthroplasty, mechanical prophylaxis, cost-effectiveness